PERLINDUNGAN HUKUM BAGI KORBAN MAIN HAKIMSENDIRI DI TINJAU DARI PRESFEKTIF VIKTIMOLOGI - Siti Duwi Lestari; Reza Agusti; Aster Sharon Destamara; Yusuf Sefudin (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2023)
Lately, there has been a lot of news in the media, both online and conventional media, about the crime ofvigilantism. Vigilantism is an action that can harm the perpetrator and even set a bad precedent for othercommunities. This results in the behavior of criminals being imitated when encountered or found by thecommunity when they commit crimes in their own environment. Public unrest against the crimes that areoften encountered makes some people who feel their security, peace of mind is disturbed and no longer trustlaw enforcement officials, so they take the law into their own hands against the perpetrators of crimeswithout following the applicable legal process. In these conditions, the role and function of the police toprevent actions that lead to vigilantism becomes important.